Hello! I have been busting my head over this question and can't for some reason solve it. Can anyone explain to me how it works or how to compute the answer.The question I am reffering to is number 5 both A and B
Thx in advance!
Hello! I have been busting my head over this question and can't for some reason solve it. Can anyone explain to me how it works or how to compute the answer.The question I am reffering to is number 5 both A and B
Thx in advance!
his answer is very good, however its just the part where it says f(fx) that i get slightly confused at. Like what exactly are we plugging in. Is it like based off the original rule
1 for x does not equal 0
f(x)= -1 for x equals 0
so when we do f(fx) is that essentialy defined as
h(x)= ????? for x=0
????? for x does not equal 0
so f(f(0) is f(-1)---> which is = 1
and f(f(4) is f(1)---> which is = 1
so h(x)=1
I'm I on the right track?
If $\displaystyle f(x) = \left\{ {\begin{array}{rl}
{1,} & {x \ne 0} \\ {-1,} & {x = 0} \\ \end{array} } \right.$ then $\displaystyle f\left( {f(x)} \right) = 1\quad ,\left( {\forall x} \right)$
Example: $\displaystyle f\left( {f(2)} \right) =f\left( 1 \right) =1$
$\displaystyle f\left( {f(0)} \right) =f\left( -1 \right) =1$
$\displaystyle f\left( {f(-2)} \right) =f\left( 1 \right) =1$.